Seismic response of SSSI system: surface structures and subway. Issue 2 (30th May 2018) - Miao, Yu; Zhong, Yi; Chen, Xixi; Ruan, Bin
Abstract : The seismic response of an underground structure is analysed in the time domain by considering the non-linearity of soil and the structure–soil–underground structure interaction. A three-dimensional model that comprises a subway station and adjacent surface frame structure with a pile foundation and soft clay is established. The modified Davidenkov model is used to simulate the non-linearity of soft clay, which is then further developed using the commercial software Abaqus. This study focuses on the influence of adjacent surface frame structures on the seismic response of a subway station in the time domain. The interstorey drift ratio of the subway station is selected to evaluate the correlation effect in this complicated system. The influence factors, including the horizontal distance between the frame structures and subway station, length of the pile foundation, orientation of the frame structure and burial depth of the subway station, are discussed in the paper. Numerical results indicate that horizontal distance and burial depth are two of the key factors that may evidently amplify or attenuate the seismic response of an underground structure.